The computer simulation of hoarfrost's clearing process in the air recuperation system; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Savrasov F. V. Fedor Vitalievich (2017, 2017)
Title screen